2007
DOI: 10.1007/s10494-007-9083-5
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Turbulent Boundary Layer in a Shrouded Rotating System

Abstract: A three-dimensional direct numerical simulation is combined with a laboratory study to describe the turbulent flow in an enclosed annular rotor-stator cavity characterized by a large aspect ratio G = (b − a)/ h = 18.32 and a small radius ratio a/b = 0.152, where a and b are the inner and outer radii of the rotating disk and h is the interdisk spacing. The rotation rate considered is equivalent to the rotational Reynolds number Re = b 2 /ν = 9.5 × 10 4 (ν the kinematic viscosity of water). This corresponds to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The authors concluded that their study indicated that the features of 3DTBLs depend on the flow configuration in question. In two very recent studies, Randriamampianina and Poncet [21] and Poncet and Randriamampianina [22] performed an experimental and numerical (DNS) investigation of turbulence characteristics in an enclosed rotor-stator system. The typical reduction in the structure parameter and the non-alignment of the velocity gradient and turbulent shear stress angles were observed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that their study indicated that the features of 3DTBLs depend on the flow configuration in question. In two very recent studies, Randriamampianina and Poncet [21] and Poncet and Randriamampianina [22] performed an experimental and numerical (DNS) investigation of turbulence characteristics in an enclosed rotor-stator system. The typical reduction in the structure parameter and the non-alignment of the velocity gradient and turbulent shear stress angles were observed.…”
Section: Introductionmentioning
confidence: 99%
“…(3)容器と円板の間に,軸方向と共に半径方向に隙間を持つ流れ. ここで,(1) における隙間が狭い流れにおいては,例えば,Cros, Le Gal (1) は,レイノルズ数の増加に伴い,同 心円状の渦,スパイラル渦,スポット状の乱流が現れることを実験的に見出している.また,隙間が広い場合に は,Aubry ら (2) が,スパイラル渦の癒着,分離現象を実験的に明らかにしており,また,Cros ら (3) は,Hopf 分岐 がスパイラル渦をもたらすことを観測している.(2)は,軸を中心に回転する円柱容器内の流体挙動に関する回転 コンテナの研究や,軸を中心に回転する円環容器内の流体挙動に関する円環キャビティの研究である.円柱コン テナにおいては,Lopez ら (4) は,静止円板上のベデバルト層の流れが不安定化することを見出し,また, 円環キ ャビティにおいては,例えば Poncet,Randriamampianina (5) が,速度分布,乱流構造を調べている.…”
unclassified